Efficient and Environmentally Sustainable Heterogeneous Polystyrene Divinylbenzene-Supported Sulphanilic Acid Catalyst for the Synthesis of Imidazopyridine Derivatives - Sunil B Hiwale (International Journal of Scientific Research in Science and Technology, 2025)
We report a recyclable Brønsted-acid catalyst consisting of sulphanilic acid covalently immobilized on a cross-linked polystyrene–divinylbenzene matrix (PS–DVB–SA). The material promotes the solvent-free two-component creation of imidazo[1,2-a]pyridines from 2-aminopyridines, aldehydes, and isocyanides at 80 °C, delivering products in 81–93% isolated yields within 27–79 min. Comprehensive characterization (FT-IR, 1H NMR and 13C NMR) confirms functional groups and presence of attachment of H-atom and C-atom environment. The catalyst is magnet-free, easy to filter, and reusability of catalyst done for at least five cycles without considerable loss. This work unites the known pharmacological relevance of imidazo[1,2-a]pyridines and the powerful Groebke–Blackburn–Bienaymé (GBB) multicomponent logic with a robust, industry-familiar PS-DVB platform, offering a practical route to scalable, low-waste heterocycle synthesis.
Keywords: imidazo[1,2-a]pyridine; multicomponent reaction; polymer-supported acid; polystyrene–divinylbenzene; sulphanilic acid; green chemistry